Population-based colorectal cancer screening: comparison of two fecal occult blood test - Zubero, Miren Begoña; Arana-Arri, Eunate; Pijoan, José Ignacio; Portillo, Isabel; Idigoras, Isabel; Lopez-Urrutia, Antonio; Samper, Ana; Uranga, Begoña; Rodriguez, Carmen; Bujanda, Luis (Frontiers in Pharmacology, 2014)
Background: The aim of screening for colorectal cancer is to improve prognosis by the detection of cancer at its early stages. In order to inform the decision on the specific test to be used in the population-based programme in the Basque Autonomous Region (Spain), we compared two immunochemical faecal occult blood quantitative tests (I-FOBT). Methods: Residents of selected study areas, aged 50-69 years, were invited to participate in the screening. Two tests based on latex agglutination (OC-Sensor and FOB Gold) were randomly assigned to different study areas. A colonoscopy was offered to patients with a positive test result. The cut-off point used to classify a result as positive, according to manufacturer’s recommendations, was 100 ng/ml for both tests. Results: The invited population included 37,999 individuals. Participation rates were 61.8% (n=11,162) for OC-Sensor and 59.1% (n=11,786) for FOB Gold, (p=0.008). Positive rate for OC-Sensor was 6.6% (n=737) and 8.5% (n=1,002) for FOB Gold, (p< 0.0001). Error rates were higher for FOB gold (2.3%) than for OC-Sensor (0.2%), (p< 0.0001). Predictive Positive Value (PPV) for total malignant and premalignant lesions was 62.4% for OC-Sensor and 58.9% for FOB Gold, (p=0.137), respectively. Conclusions: OC-Sensor test appears to be superior for I-FOBT based CRC screening, given its acceptance, ease of use, associated small number of errors and its screening accuracy. FOB-Gold on the other hand, has higher rate of positive values, with more colonoscopies performed, it shows higher detection incidence rates, but involves more false positives.